A Quasi-Experimental Research on Middle Schools’ Students Writing Skill Development Through the Power of Flipped Classroom Method - Hasani, M. Tanwirul; Usuluddin, Usuluddin; Prasetyaningrum, Ari; Nazri, M. Adib (Universitas Pahlawan Tuanku Tambusai, 2024)
This study explored the effectiveness of the Flipped Classroom method in improving writing skills among students at MTs Hizbul Wathan NW Semaya, employing a quasi-experimental design. By transforming the traditional learning approach, this method allowed students to study instructional materials independently before collaborating in the classroom. The research involved pre- and post-test assessments of students' writing abilities, revealing a notable enhancement in the experimental group's performance compared to the control group. Specifically, the experimental group achieved a mean post-test score of 82.18, while the control group's mean was 60.33. These results highlighted the Flipped Classroom's ability to foster greater student engagement, motivation, and confidence in writing. The article also addressed the implications of these findings for future teaching practices and emphasized the importance of further research to assess the long-term impact of this method across different educational settings. Overall, the study supported the Flipped Classroom approach as an effective strategy for advancing students' writing proficiency and enhancing their overall language skills.